2014
DOI: 10.3389/fneur.2014.00225
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Lennox–Gastaut Syndrome as a Secondary Network Epilepsy

Abstract: Lennox–Gastaut Syndrome (LGS) is a category of severe, disabling epilepsy, characterized by frequent, treatment-resistant seizures, and cognitive impairment. Electroencephalography (EEG) shows characteristic generalized epileptic activity that is similar in those with lesional, genetic, or unknown causes, suggesting a common underlying mechanism. The condition typically begins in young children, leaving many severely disabled with recurring seizures throughout their adult life. Scalp EEG of the tonic seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 127 publications
2
65
0
1
Order By: Relevance
“…Functional neuroimaging has indicated that epileptic activity in LGS recruits widespread areas of association cortex and that tonic seizures are expressed through the reticular formation of the pons (Archer et al, 2014). LGS has been recently conceptualized as "secondary network epilepsy" in which the epileptic activity is expressed through largescale brain networks; cortical lesions, when present, appear to chronically interact with these networks to produce M. Koutroumanidis, et al network instability rather than triggering each individual epileptic discharge (Archer et al, 2014). There is significant overlap between LGS and other epilepsy syndromes (Kaminska and Oguni, 2013), making the differential diagnosis particularly challenging.…”
Section: Overviewmentioning
confidence: 99%
“…Functional neuroimaging has indicated that epileptic activity in LGS recruits widespread areas of association cortex and that tonic seizures are expressed through the reticular formation of the pons (Archer et al, 2014). LGS has been recently conceptualized as "secondary network epilepsy" in which the epileptic activity is expressed through largescale brain networks; cortical lesions, when present, appear to chronically interact with these networks to produce M. Koutroumanidis, et al network instability rather than triggering each individual epileptic discharge (Archer et al, 2014). There is significant overlap between LGS and other epilepsy syndromes (Kaminska and Oguni, 2013), making the differential diagnosis particularly challenging.…”
Section: Overviewmentioning
confidence: 99%
“…1 Given that diverse causes result in a shared electroclinical profile, we and others have hypothesized that the epileptic process in LGS may engage common brain systems. [2][3][4][5] Clinical observations suggest that epileptic activity can contribute directly to impaired cognition in LGS, a process termed "epileptic encephalopathy." 5 Patients with LGS typically experience cognitive regression at seizure onset, and intellectual decline often continues if seizures remain poorly controlled.…”
mentioning
confidence: 99%
“…[12] Although paroxysmal fast activities are not pathognomonic for LGS because these activities may also be observed in focal lesional epilepsy, paroxysmal fast activities are suggestive of LGS, especially with bilateral GPFA. [29] All of our patients had GPFA. Interestingly, GPFA were especially observed during sleep, which was consistent with the previous study.…”
Section: Discussionmentioning
confidence: 96%